2017
DOI: 10.1016/j.foodchem.2017.04.133
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation structures based on protein-coated liposomes obtained through electrospraying for the stabilization and improved bioaccessibility of curcumin

Abstract: Novel food-grade hybrid encapsulation structures based on the entrapment of phosphatidylcholine liposomes, within a WPC matrix through electrospraying, were developed and used as delivery vehicles for curcumin. The loading capacity and encapsulation efficiency of the proposed system was studied, and the suitability of the approach to stabilize curcumin and increase its bioaccessibility was assessed. Results showed that the maximum loading capacity of the liposomes was around 1.5% of curcumin, although the load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(47 citation statements)
references
References 42 publications
(42 reference statements)
4
41
0
Order By: Relevance
“…The microparticles obtained were spherical with a diameter of nearly 1 µm. This study showed that whey-protein microparticles can protect curcumin from degradation in PBS buffer (pH 7.4) and curcumin-liposome digestion in the gastrointestinal environment [162]. Jyoti et al synthesized curcumin complexed with 2-hydroxylpropyl-β-cyclodextrin loaded in chitosan microspheres by the emulsion-polymerization technique.…”
Section: Microcarriers For Curcumin Deliverymentioning
confidence: 97%
“…The microparticles obtained were spherical with a diameter of nearly 1 µm. This study showed that whey-protein microparticles can protect curcumin from degradation in PBS buffer (pH 7.4) and curcumin-liposome digestion in the gastrointestinal environment [162]. Jyoti et al synthesized curcumin complexed with 2-hydroxylpropyl-β-cyclodextrin loaded in chitosan microspheres by the emulsion-polymerization technique.…”
Section: Microcarriers For Curcumin Deliverymentioning
confidence: 97%
“…Liposome dispersions in water, similar to those produced in Gómez-Mascaraque, Casagrande Sipoli, et al (2017), were also produced for comparison purposes, by replacing the acetic acid 20% (v/v) with MilliQ water.…”
Section: Liposomes Productionmentioning
confidence: 99%
“…The lipids' 211 spectrum was obtained without further processing in ATR mode. Each recorded spectrum 212 was determined from an average of 16 scans at 4 cm -1 resolution (Gómez-Mascaraque, Casagrande Sipoli, et al, 2017).…”
Section: Fourier Transform Infrared (Ft-ir) Analysismentioning
confidence: 99%
“…The proposed approach thus proved to be a promising alternative to produce powder-like functional ingredients [33].…”
Section: Stabilitymentioning
confidence: 98%
“…Microencapsulation of curcumin within hybrid structures, consisting of curcumin‐loaded liposomes within a protein matrix, significantly increased its bioaccessibility (∼1.seven‐fold) compared to the free compound, and could successfully stabilize it against degradation in PBS (pH = 7.4). The proposed approach thus proved to be a promising alternative to produce powder‐like functional ingredients .…”
Section: Physico‐chemical Properties Of Curcuminmentioning
confidence: 99%